Kajian Filosofis tentang Alasan Mendesak pada Perkara Dispensasi Nikah di Pengadilan Agama - mahmudah, Roiha (ABHATS: Jurnal Islam Ulil Albab, 2025)
Law No. 16 of 2019 stipulates that a marriage dispensation may be requested by parents or a child’s guardian to the Religious Court based on urgent reasons, which must be proven during trial. Urgent reasons are understood as circumstances in which no other option exists except for the immediate solemnization of marriage. This study aims to philosophically examine the concept of urgent reasons in marriage dispensation cases within the Religious Court. The method employed is qualitative research with philosophical and juridical-normative approaches. The findings indicate that urgent reasons commonly submitted include premarital pregnancy, promiscuity or intimate relationships before marriage, weak family economic conditions, cultural or customary factors such as arranged marriages, and efforts to prevent acts of zina (fornication). Judges’ considerations in deciding marriage dispensation cases are based on the relevance of the reasons submitted to the facts revealed in court and the testimony of witnesses. Therefore, judicial prudence is essential, as such cases are closely related to the implementation of maqāṣid al-sharī‘ah, particularly ḥifẓ al-nasl (preservation of lineage), which necessitates that not every dispensation request should be readily granted. [Undang-Undang Nomor 16 Tahun 2019 menyatakan bahwa dispensasi kawin dapat diajukan oleh orang tua atau wali anak ke Pengadilan Agama dengan alasan mendesak yang harus dibuktikan melalui persidangan. Alasan mendesak dimaknai sebagai kondisi di mana tidak terdapat pilihan lain selain segera dilangsungkannya perkawinan. Penelitian ini bertujuan mengkaji secara filosofis konsep alasan mendesak dalam perkara dispensasi nikah di Pengadilan Agama. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan filosofis dan yuridis-normatif. Hasil kajian menunjukkan bahwa alasan mendesak yang kerap diajukan meliputi kehamilan di luar nikah, pergaulan bebas atau hubungan intim pranikah, kondisi ekonomi keluarga yang lemah, faktor budaya atau adat seperti perjodohan, serta upaya menghindari perbuatan zina. Pertimbangan hakim dalam memutus perkara dispensasi nikah didasarkan pada penilaian terhadap kesesuaian alasan yang diajukan dengan fakta persidangan dan keterangan saksi. Oleh karena itu, kehati-hatian hakim sangat diperlukan mengingat perkara ini berkaitan dengan implementasi maqāṣid al-syarī‘ah, khususnya ḥifẓ al-nasl (menjaga keturunan), sehingga tidak semua permohonan dispensasi dapat serta-merta dikabulkan.]